2020
DOI: 10.1155/2020/3415471
|View full text |Cite
|
Sign up to set email alerts
|

Astragalus membranaceus–Derived Anti-Programmed Death-1 Monoclonal Antibodies with Immunomodulatory Therapeutic Effects against Tumors

Abstract: Astragalus membranaceus polysaccharide (APS) components are main ingredients of TCM and have proven efficacy to activate T cells and B cells, enhancing immunity in humans. In this study, elevated cytokine and anti-PD-1 antibody titers were found in mice after immunization with APS. Therefore, phage-display technology was utilized to isolate specific anti-programmed death-1 (PD-1) antibodies from mice stimulated by APS and to confirm whether the isolated anti-PD-1 antibody could inhibit the interaction of PD-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Cosignalling receptors, including costimulatory and coinhibitory receptors, play an indispensable role in regulating the immune response [ 5 ]. Coinhibitory receptors, such as programmed cell death protein-1 (PD-1) and cytotoxic T lymphocyte associated-4 (CTLA-4), have been reported to correlate with Treg dysfunction and participate in evading immune surveillance [ 6 8 ]. Conversely, costimulatory receptors such as CD28, OX40, and 4-1BB have also been widely implicated in T cell stimulation and immune homeostasis [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cosignalling receptors, including costimulatory and coinhibitory receptors, play an indispensable role in regulating the immune response [ 5 ]. Coinhibitory receptors, such as programmed cell death protein-1 (PD-1) and cytotoxic T lymphocyte associated-4 (CTLA-4), have been reported to correlate with Treg dysfunction and participate in evading immune surveillance [ 6 8 ]. Conversely, costimulatory receptors such as CD28, OX40, and 4-1BB have also been widely implicated in T cell stimulation and immune homeostasis [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In China, herbal medicine is frequently combined with other treatments to reduce adverse effects (11,12), improve patient quality-of-life, and prolong survival. Many natural products that originate from Chinese herbal medicine exhibit anticancer activities (13)(14)(15), including antiproliferative, pro-apoptotic, antimetastatic, and anti-angiogenic effects. These products have been shown to regulate autophagy, reverse multidrug resistance, balance immunity, and enhance chemotherapy in vitro and in vivo (16).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the rise of immune agents, the immunomodulatory function of traditional Chinese medicine on immune checkpoints has also aroused great interest. Previous studies (Chang F.-L. et al, 2020) have shown that APS can significantly inhibit the growth of melanoma cells in transgenic mice and reduce the expression of PD-L1 in tumors, suggesting that the anti-tumor immunosuppressive mechanism of APS may also be related to the regulation of PD-1/PD-L1 signal pathway. A study demonstrated that there was no significant difference in tumor inhibition compared with anti-PD-1 combined with ixabepilone or APS, indicating that APS can maintain an effective dose of anti-PD-1 antibody in vivo, and delay the progression of tumor or tumorigenesis by increasing the activity of T cells, which may improve the synergistic effect (Chang F.-L. et al, 2020).…”
Section: Astragalus Polysaccharidesmentioning
confidence: 97%
“…Previous studies (Chang F.-L. et al, 2020) have shown that APS can significantly inhibit the growth of melanoma cells in transgenic mice and reduce the expression of PD-L1 in tumors, suggesting that the anti-tumor immunosuppressive mechanism of APS may also be related to the regulation of PD-1/PD-L1 signal pathway. A study demonstrated that there was no significant difference in tumor inhibition compared with anti-PD-1 combined with ixabepilone or APS, indicating that APS can maintain an effective dose of anti-PD-1 antibody in vivo, and delay the progression of tumor or tumorigenesis by increasing the activity of T cells, which may improve the synergistic effect (Chang F.-L. et al, 2020). In addition, another research showed that APS enhances the chemotherapy by stimulating host immunity through reducing the PD-L1 expression of tumor surface (Chang H.-L. et al, 2020).…”
Section: Astragalus Polysaccharidesmentioning
confidence: 97%
See 1 more Smart Citation